Hydrofining catalyst as well as preparation method and application thereof
During the regeneration process of wind turbine gear lubricant, the hydrorefining catalyst prepared by using large pore squid squid, pore reamers and alkaline glue solvents, the problems of large mass transfer resistance and small pore size are solved, and the problem of large mass transfer resistance and small pore size is achieved. Efficient lubricant regeneration and reduced operating costs.
Patent Information
- Application Number
- CN202311026506.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-15
- Publication Date
- 2025-02-21
AI Technical Summary
The existing hydrogenation purification catalyst has a large mass transfer resistance during the regeneration of gear lubricant of wind turbine generators, which affects the reaction efficiency. The conventional catalyst has a small pore size and a large diffusion resistance, making it difficult to effectively reduce the cost of regeneration of lubricant.
A catalyst is prepared under alkaline conditions through a gelatinization reaction to form a hydropurification catalyst with large pore size and large pore volume.
Improves the mass transfer efficiency of the hydrogenation and refining process of wind turbine gear lubricant, improves the reaction airspeed, reduces operating costs, and is better than the acid value, sulfur content and content of conventional engine lubricant hydrochloricant refining catalysts. Indicators such as phosphorus.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fan gear lubricating oil regeneration, and in particular relates to a preparation method, a use method and application of a hydrorefining catalyst for fan gear lubricating oil regeneration. Background Art
[0002] Wind power generation is a form of clean and renewable energy conversion that converts the kinetic energy of wind into electrical energy. It is an important part of new energy. The main gearbox of a wind turbine is the core component of the transmission chain of the whole machine. Its main function is to transmit the power generated by the rotation of the blades to the generator through the gear pair speed increaser. Wind power generation is mostly located in remote areas. The lubrication of the gearbox is of great significance to the long-term stable operation of wind turbines. The lubricating oil of wind turbine gears cannot be replaced frequently, and its service life is required to be 5-7 years. In addition, the lubricating oil of wind power gearboxes is required to have high load-bearing capacity, good antioxidant properties, and high anti-micropitting ability, as well as low foaming, shear resistance, and high and low temperature adaptability. Based on the above factors, the base oil of wind turbine gear lubricating oil is different from that of engine lubricating oil. It is necessary to use polyalphaolefin (PAO) fully synthetic base oil and high-performance composite additives. The main component of PAO monomer is 1-decene, which is a polymer with a molecular weight of about 3000 after polymerization. Compared with engine lubricating oil, it has the characteristics of high viscosity and large molecular weight.
[0003] The amount of lubricating oil used in wind turbine gearboxes is 300-600L / unit, and it needs to be replaced when it reaches its service life. The amount of inferior waste lubricating oil replaced every year is very large, and improper disposal will cause environmental pollution. The main reason for the deterioration of lubricating oil in wind turbine gearboxes is the failure of additives, while the PAO base oil as the main body of lubricating oil still maintains a good molecular structure and can be recycled and reused. According to the "Catalogue of Comprehensive Utilization of Resources" promulgated by the state, support the regeneration and comprehensive resource utilization of waste lubricating oil, and encourage the research and development of new technologies and processes for the comprehensive utilization of waste oil. Considering the recovery rate of base oil, oil quality, environmental protection and other aspects, the most advanced lubricating oil regeneration technology at present is hydrofining regeneration, that is, under the action of a catalyst, under certain temperature and pressure conditions, through hydrogenation reaction, the purpose of desulfurization, dephosphorization and deoxygenation is achieved. The product is separated from the base oil PAO through a subsequent distillation process, and the separated PAO is re-blended with new additives to achieve regeneration.
[0004] The PAO used in the base oil of wind turbine gear lubricant is characterized by large molecular weight and high viscosity (kinematic viscosity at 40°C can reach 1700mm 2 / s), conventional hydrotreating catalysts are for mineral oil, low viscosity PAO synthetic oil (40℃ kinematic viscosity less than 100mm 2 / s). Conventional hydrorefining catalysts have small pore sizes and small pore volumes. In the hydrorefining process of wind turbine gear lubricating oil, the diffusion resistance is large, which affects the reaction efficiency. Therefore, it is urgent to develop a special catalyst suitable for wind turbine gear lubricating oil hydrorefining with significantly better performance than conventional lubricating oil hydrorefining catalysts. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a hydrorefining catalyst for regenerating wind turbine gear lubricating oil. The catalyst has a relatively large pore size, which is beneficial to reducing the mass transfer resistance of the macromolecular wind turbine gear lubricating oil in the catalyst and reducing the regeneration cost of the lubricating oil.
[0006] To achieve the above purpose, the present invention adopts the following technical solutions:
[0007] The first aspect of the present invention provides a method for preparing a hydrotreating catalyst, comprising the following steps:
[0008] (1) mixing macroporous pseudo-boehmite, a nickel or cobalt oxide precursor, a molybdenum or tungsten oxide precursor, and a phosphorus oxide precursor to obtain a primary mixture;
[0009] (2) adding the alcohol solution of the pore-enlarging agent to the primary mixture and continuing to mix to obtain a mixture;
[0010] (3) adding an alkaline peptizing agent and water to the mixed material, maintaining the pH value at 9-12, to obtain a mixed material;
[0011] (4) kneading the mixed material into a plastic body, extruding strips, and obtaining a molding material;
[0012] (5) drying and calcining the molded material to obtain the hydrotreating catalyst;
[0013] The pore size of the macroporous pseudo-boehmite is ≥10nm; the pore volume is ≥1.0cm 3 / g.
[0014] Since the base oil of wind turbine gear lubricating oil is high-viscosity and high-molecular-weight polyalphaolefin (PAO) with a molecular weight of about 3,000, it is not conducive to mass transfer in the catalyst pores. The present invention adopts macroporous pseudo-boehmite, a pore-enlarging agent and an alkaline peptizing agent, maintains the pH at 9-12, and obtains a mixed material; the mixed material is subjected to kneading, extrusion, drying, roasting and other processes to prepare a hydrorefining catalyst with large pore size and large pore volume. It is beneficial to improve the mass transfer efficiency of the hydrorefining regeneration process of wind turbine gear lubricating oil, increase the reaction space velocity, and reduce the operating cost.
[0015] In order to prepare a hydrotreating catalyst with a larger pore size, the present invention adds a pore expander. In some preferred embodiments, the pore expander is polyethylene glycol; preferably, the pore expander is polyethylene glycol 3000, polyethylene glycol 4000, polyethylene glycol 6000 or polyethylene glycol 8000; in order to achieve a better pore expansion effect and take into account the economic cost, preferably, the amount of the pore expander added is 8-20wt% of the macroporous pseudo-boehmite, preferably 10-15wt% of the macroporous pseudo-boehmite; and / or
[0016] The alcohol solution of the pore expanding agent is a C1-C4 saturated monohydric fatty alcohol solution of the pore expanding agent, preferably an ethanol solution of the pore expanding agent.
[0017] In order to further facilitate the mass transfer of PAO in the catalyst pores and make the catalyst have a larger pore size, the mixed material in the present application needs to maintain a pH of 9-12. Therefore, it is necessary to add an alkaline peptizing agent. Acidic peptizing agents such as nitric acid are usually used in the prior art. The addition of these acidic peptizing agents will make the peptization reaction violent and difficult to control, but will cause the macroporous pseudo-boehmite to reorganize, thereby reducing its pore size, and it is difficult to form the hydrorefining catalyst with large pore size and large pore volume described in the present invention. However, the present application adds an alkaline peptizing agent, and the mixed material needs to maintain a pH of 9-12, and the peptization reaction is gentle and easy to control, which can effectively maintain the larger pore size of the macroporous pseudo-boehmite, thereby obtaining a hydrorefining catalyst with large pore size and large pore volume.
[0018] In some preferred embodiments, the alkaline peptizing agent is aqueous ammonia, triethylamine or ethylenediamine; preferably, the amount of the alkaline peptizing agent added is 2-20wt% of the mixture; more preferably, the amount of the alkaline peptizing agent added is 3-16wt% of the mixture; more preferably, the peptization reaction time of the mixture is 0.5-1.0h.
[0019] In some preferred embodiments, the pore size of the macroporous pseudo-boehmite is 10-12 nm, and the pore volume is 1.0-1.2 cm 3 / g, specific surface area is 350-400m 2 / g.
[0020] The present invention is different from the traditional method for preparing catalysts, such as the impregnation method. The traditional impregnation method uses acidic conditions. Because under alkaline conditions, metal elements are not easy to maintain and are easy to form precipitation forms, resulting in the impregnation solution actually not containing all metal elements. Therefore, some precipitated metal elements cannot form catalyst components at all. The present application is not suitable for the use of acidic conditions, and the reasons have been mentioned above. Therefore, the present application does not adopt the impregnation method, but uses macroporous pseudo-boehmite and oxide precursors of each metal to mix evenly in the solid state, and then adds a pore expander and an alkaline peptizing agent, and the initial mixed material is peptized to obtain a mixed material.
[0021] In some preferred embodiments, the oxide precursor of nickel is basic nickel carbonate or nickel hydroxide; the oxide precursor of cobalt is basic cobalt carbonate or cobalt hydroxide; the oxide precursor of molybdenum is ammonium heptamolybdate or ammonium tetramolybdate; the oxide precursor of tungsten is ammonium tungstate or ammonium metatungstate; and the oxide precursor of phosphorus is diammonium phosphate.
[0022] In some preferred embodiments, based on the total weight of the hydrotreating catalyst, the content of NiO or Co2O3 is 5-10wt%, the content of MoO3 or WO3 is 20-28wt%, the content of P2O5 is 5-8wt%, and the content of Al2O3 is 54-70wt%.
[0023] The present invention uses macroporous pseudo-boehmite and oxide precursors of various metals to mix evenly in a solid state, then adds a pore expander and an alkaline peptizing agent, and maintains a pH of 9-12. Under the action of the alkaline peptizing agent and water, the macroporous pseudo-boehmite begins to partially peptize, and the mixed material gradually becomes sticky. The mixed material is kneaded into a plastic body and extruded to obtain a molding material. In the extrusion process, the mold used is a clover-shaped mold with an opening diameter of 1.5-3mm. The molding material is dried at a temperature of 100-120°C for 2-5h; and roasted at a temperature of 400-600°C for 3-5h.
[0024] The second aspect of the present invention provides a hydrorefining catalyst. It is prepared by the above-mentioned preparation method; preferably, the hydrorefining catalyst has a pore diameter of 12-18 nm and a pore volume of 0.5-0.8 cm 3 / g, BET specific surface area is 100-203m 2 / g.
[0025] The third aspect of the present invention provides the hydrotreating catalyst prepared by the aforementioned preparation method or the use of the aforementioned hydrotreating catalyst in the hydrotreating of lubricating oil, wherein the lubricating oil is preferably waste lubricating oil of fan gears.
[0026] The fourth aspect of the present invention provides a method for hydrofining waste lubricating oil of fan gears, wherein the hydrofining method uses the hydrofining catalyst prepared by the aforementioned preparation method or the aforementioned hydrofining catalyst; preferably, before use, the hydrofining catalyst is introduced with sulphurized oil having a CS2 mass fraction of 1-10% and H2 for in-situ sulphurization, and the sulphurization conditions are: temperature of 300-340°C, mass space velocity of 1-3h -1 , pressure is 4.0-6.0MPa, hydrogen-oil ratio is 400:1-800:1, and time is 4-8h.
[0027] Preferably, the hydrofining method includes the following reaction conditions: temperature of 250-350°C, pressure of 5.0-15.0 MPa, mass space velocity of 0.5-1.5 h -1 , the hydrogen-to-oil ratio is 400:1-800:1.
[0028] The technical solution provided by the present invention has the following beneficial effects:
[0029] The present invention provides a method for preparing a hydrorefining catalyst, which comprises mixing macroporous pseudo-boehmite with various metal oxide precursors in a solid state, adding a pore-expanding agent and an alkaline peptizing agent, maintaining the pH at 9-12, and performing a peptization reaction for 0.5-1.0h to obtain a mixed material, and preparing the hydrorefining catalyst through kneading, extrusion, drying, roasting and other processes. The hydrorefining catalyst has a pore diameter of 12-18nm and a pore volume of 0.5-0.8cm 3 / g, BET specific surface area is 100-203m 2 / g. Compared with the traditional impregnation method hydrofining catalyst, this catalyst adopts solid mixing of metal oxide precursors, and the metal elements are evenly distributed. It adopts alkaline peptizing agent and maintains pH at 9-12. The peptization reaction is mild and easy to control, which can effectively maintain the larger pore size of macroporous pseudo-boehmite. Since the prepared catalyst has the characteristics of large pore size and large pore volume, it is beneficial to improve the mass transfer efficiency of the hydrofining regeneration process of waste wind turbine gear lubricating oil, increase the reaction space velocity, and reduce the operating cost. Under the same reaction space velocity, reaction pressure, reaction temperature, and hydrogen-to-oil ratio, the acid value, sulfur content, phosphorus content and other indicators as key indicators of the regenerated lubricating oil are better than those of conventional engine lubricating oil hydrofining regeneration catalysts. DETAILED DESCRIPTION
[0030] The present invention is further described below by means of specific embodiments. The embodiments of the present invention are only used as illustrations of the present invention and do not mean that the scope of the present invention is limited thereto.
[0031] In the following examples, the preparation method of the hydrotreating catalyst specifically comprises the following steps:
[0032] (1) Mixing macroporous pseudo-boehmite, a nickel or cobalt oxide precursor, a molybdenum or tungsten oxide precursor, and a phosphorus oxide precursor to obtain a primary mixture; based on the total weight of the hydrorefining catalyst, the content of NiO or Co2O3 is 5-10wt%, the content of MoO3 or WO3 is 20-28wt%, the content of P2O5 is 5-8wt%, and the content of Al2O3 is 54-70wt%. The macroporous pseudo-boehmite has a pore size of ≥10nm and a pore volume of ≥1.0cm 3 / g.
[0033] (2) dissolving polyethylene glycol in ethanol, adding the ethanol solution of polyethylene glycol to the primary mixture and continuing to mix to obtain a mixture; the amount of polyethylene glycol added is 8-20 wt % of the macroporous pseudo-boehmite.
[0034] (3) adding an alkaline peptizing agent and water to the mixture, maintaining the pH at 9-12, and stirring to obtain a mixture; the alkaline peptizing agent is ammonia water, triethylamine or ethylenediamine; the amount of the alkaline peptizing agent added is 2-20wt% of the mixture, and the peptization reaction time of the mixture is 0.5-1.0h
[0035] (4) kneading the mixed material into a plastic body and extruding strips to obtain a molded material; in the strip extrusion process of step (4), the mold used is a clover-shaped mold with an opening diameter of 1.5-3mm.
[0036] (5) Drying at 100-120°C for 2-5h; calcining at 400-600°C for 3-5h. The pore size of the hydrorefining catalyst is 12-18nm and the pore volume is 0.5-0.8cm 3 / g, BET specific surface area is 100-203m 2 / g.
[0037] In the following examples, the method for using the hydrotreating catalyst prepared by the above preparation method includes:
[0038] The catalyst should be sulfurized before use, and sulfurized oil with a CS2 mass fraction of 1-10% and H2 are introduced for in-situ sulfurization to sulfurize nickel, cobalt, molybdenum or tungsten metal oxides into sulfides; the sulfurization conditions are: temperature of 300-340°C, mass space velocity of 1-3h -1 , pressure is 4.0-6.0MPa, hydrogen-oil ratio is 400:1-800:1, and time is 4-8h.
[0039] The sulfided catalyst is then subjected to a hydrorefining reaction. The reaction conditions for the hydrorefining reaction are: temperature 250-350°C, pressure 5.0-15.0MPa, and mass space velocity 0.5-1.5h -1 , the hydrogen-to-oil ratio is 400:1-800:1.
[0040] Reagents and instruments:
[0041] Macroporous pseudo-boehmite was purchased from Yantai Henghui Chemical Co., Ltd., model YH-05, with an Al2O3 content of 72.5wt%, a pore diameter of 11nm, and a pore volume of 1.07cm 3 / g, specific surface area is 385m 2 / g; Chalco Shandong Co., Ltd., model P-DF-03, Al2O3 content is 66%, pore diameter is 4.19nm, pore volume is 0.27cm3 / g, specific surface area is 253m 2 / g.
[0042] The specific surface area of the sample was measured by a nitrogen physical adsorption instrument, which was purchased from Micromeritics Company and had a model of tristarII 3020-M.
[0043] The muffle furnace was purchased from Thermo Scientific, model FD1500.
[0044] The composition of the catalyst was measured using a ZSX Primus II X-ray fluorescence spectrometer (XRF) from Rigaku Corporation.
[0045] The hydrotreating reaction evaluation device was purchased from Beijing Sixintong Technology Co., Ltd.
[0046] Example 1
[0047] Weigh 300 g of macroporous pseudo-boehmite (YH-05), 28 g of basic nickel carbonate, 103 g of ammonium heptamolybdate, and 27 g of ammonium dihydrogen phosphate, and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0048] Weigh 40 g of polyethylene glycol 3000 and dissolve it in 50 g of ethanol. Add the ethanol solution of polyethylene glycol to the primary mixture and continue mixing to obtain a mixture. The amount of polyethylene glycol added is 13 wt % of the macroporous pseudo-boehmite.
[0049] 100 g of ammonia water (ammonia content 25%) and 10 g of deionized water were added, the pH was maintained at 10, and the mixture was stirred to undergo peptization reaction for 1.0 h to obtain a mixed material; the amount of the alkaline peptizing agent added was 15 wt % of the mixed material.
[0050] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 1.5 mm.
[0051] The catalyst was dried in an oven at 120°C for 2 hours and calcined at 500°C for 3 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 65.0wt%, MoO3 25.0wt%, NiO 5.0wt% and P2O 55.0wt%. The pore size of the catalyst is 12nm and the pore volume is 0.5cm 3 / g, BET specific surface area is 203m 2 / g.
[0052] Example 2
[0053] Weigh 300 g of macroporous pseudo-boehmite (YH-05), 42 g of basic nickel carbonate, 83 g of ammonium heptamolybdate, and 44 g of ammonium dihydrogen phosphate, and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0054] Weigh 30 g of polyethylene glycol 4000 and dissolve it in 40 g of ethanol. Add the ethanol solution of polyethylene glycol to the primary mixture and continue mixing to obtain a mixture. The amount of polyethylene glycol added is 10 wt % of the macroporous pseudo-boehmite.
[0055] 100 g of ammonia water (ammonia content 25%) and 20 g of deionized water were added, the pH was maintained at 10, and the mixture was stirred to undergo peptization reaction for 0.5 h to obtain a mixed material; the amount of the alkaline peptizing agent added was 15 wt % of the mixed material.
[0056] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 2.0 mm.
[0057] The catalyst was dried in an oven at 100°C for 5 hours and calcined at 400°C for 5 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 64.5wt%, MoO3 20.0wt%, NiO 7.5wt% and P2O 58.0wt%. The pore size of the catalyst is 15nm and the pore volume is 0.7cm 3 / g, BET specific surface area is 157m 2 / g.
[0058] Example 3
[0059] Weigh 300 g of macroporous pseudo-boehmite (YH-05), 61 g of basic nickel carbonate, 104 g of ammonium heptamolybdate, and 38 g of ammonium dihydrogen phosphate, and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0060] Weigh 45 g of polyethylene glycol 6000 and dissolve it in 50 g of ethanol, add the ethanol solution of polyethylene glycol to the primary mixture and continue mixing to obtain a mixture; the amount of polyethylene glycol added is 15 wt % of the macroporous pseudo-boehmite.
[0061] 100 g of ammonia water (ammonia content 25%) and 5 g of deionized water were added, the pH was maintained at 9, and the mixture was stirred to undergo peptization reaction for 0.5 h to obtain a mixed material; the amount of the alkaline peptizing agent added was 14 wt % of the mixed material.
[0062] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 3.0 mm.
[0063] The catalyst was dried in an oven at 110°C for 4 hours and calcined at 600°C for 4 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 60.0wt%, MoO3 23.5wt%, NiO 10.0wt% and P2O56.5wt%. The pore size of the catalyst is 18nm and the pore volume is 0.8cm 3 / g, BET specific surface area is 102m 2 / g.
[0064] Example 4
[0065] Weigh 300 g of macroporous pseudo-boehmite (YH-05), 29 g of basic nickel carbonate, 120 g of ammonium heptamolybdate, and 28 g of ammonium dihydrogen phosphate, and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0066] 800037g of polyethylene glycol was weighed and dissolved in 50g of ethanol, and the ethanol solution of polyethylene glycol was added to the primary mixture and continued to mix to obtain a mixture; the amount of polyethylene glycol added was 12wt% of the macroporous pseudo-boehmite.
[0067] 100 g of ammonia water (ammonia content 25%) and 5 g of deionized water were added, the pH was maintained at 10, and the mixture was stirred to undergo peptization reaction for 1.0 h to obtain a mixed material; the amount of the alkaline peptizing agent added was 15 wt % of the mixed material.
[0068] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 1.8 mm.
[0069] The catalyst was dried in an oven at 100°C for 5 hours and calcined at 600°C for 3 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 62.0wt%, MoO3 28.0wt%, NiO 5.0wt% and P2O55.0wt%. The pore size of the catalyst is 13nm and the pore volume is 0.6cm 3 / g, BET specific surface area is 125m 2 / g.
[0070] Example 5
[0071] Weigh 300 g of macroporous pseudo-boehmite (YH-05), 19.3 g of nickel hydroxide, 71.6 g of ammonium tetramolybdate, and 25 g of ammonium dihydrogen phosphate, and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0072] Weigh 40 g of polyethylene glycol 3000 and dissolve it in 50 g of ethanol. Add the ethanol solution of polyethylene glycol to the primary mixture and continue mixing to obtain a mixture. The amount of polyethylene glycol added is 13 wt % of the macroporous pseudo-boehmite.
[0073] 30 g of triethylamine and 80 g of deionized water were added, the pH was maintained at 9, and the mixture was stirred to undergo peptization reaction for 1.0 h to obtain a mixed material; the amount of the alkaline peptizing agent added was 5 wt % of the mixed material.
[0074] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 1.6 mm.
[0075] The catalyst was dried in an oven at 120°C for 2 hours and calcined at 400°C for 5 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 70.0wt%, MoO3 20.0wt%, NiO 5.0wt% and P2O55.0wt%. The pore size of the catalyst is 16nm and the pore volume is 0.7cm 3 / g, BET specific surface area is 138m 2 / g.
[0076] Example 6
[0077] Weigh 300 g of macroporous pseudo-boehmite (YH-05), 24.6 g of basic cobalt carbonate (cobalt content is 45%), 68.3 g of ammonium tungstate, and 25 g of diammonium phosphate, and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0078] Weigh 40 g of polyethylene glycol 3000 and dissolve it in 50 g of ethanol. Add the ethanol solution of polyethylene glycol to the primary mixture and continue mixing to obtain a mixture. The amount of polyethylene glycol added is 13 wt % of the macroporous pseudo-boehmite.
[0079] 20 g of ethylenediamine and 90 g of deionized water were added, the pH was maintained at 12, and the mixture was stirred to undergo peptization reaction for 0.5 h to obtain a mixed material; the amount of the alkaline peptizing agent added was 3 wt % of the mixed material.
[0080] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 2.5 mm.
[0081] The catalyst was dried in an oven at 110°C for 4 hours and calcined at 500°C for 4 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 70.0wt%, WO3 20.0wt%, Co2O3 5.0wt% and P2O 55.0wt%. The pore size of the catalyst is 18nm and the pore volume is 0.8cm 3 / g, BET specific surface area is 178m 2 / g.
[0082] Example 7
[0083] Weigh 300 g of macroporous pseudo-boehmite (YH-05), 19.3 g of cobalt hydroxide, 66 g of ammonium metatungstate, and 25 g of ammonium dihydrogen phosphate, and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0084] Weigh 45 g of polyethylene glycol 6000 and dissolve it in 50 g of ethanol, add the ethanol solution of polyethylene glycol to the primary mixture and continue mixing to obtain a mixture; the amount of polyethylene glycol added is 15 wt % of the macroporous pseudo-boehmite.
[0085] 100 g of ammonia water (ammonia content 25%) and 5 g of deionized water were added, the pH was maintained at 11, and the mixture was stirred to undergo peptization reaction for 1.0 h to obtain a mixed material; the amount of the alkaline peptizing agent added was 16 wt % of the mixed material.
[0086] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 2.5 mm.
[0087] The catalyst was dried in an oven at 120°C for 3 hours and calcined at 500°C for 3 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 70.0wt%, WO3 20.0wt%, Co2O3 5.0wt% and P2O 55.0wt%. The pore size of the catalyst is 17nm and the pore volume is 0.8cm 3 / g, BET specific surface area is 185m 2 / g.
[0088] Comparative Example 1
[0089] Weigh 300 g of macroporous pseudo-boehmite (YH-05), 64.5 g of nickel nitrate hexahydrate, 103 g of ammonium heptamolybdate, and 27 g of ammonium dihydrogen phosphate, and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0090] Add 120 g of deionized water and stir to obtain a mixed material;
[0091] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 1.5 mm.
[0092] The catalyst was dried in an oven at 120°C for 2 hours and calcined at 500°C for 3 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 65.0wt%, MoO3 25.0wt%, NiO 5.0wt% and P2O 55.0wt%. The pore size of the catalyst is 5nm and the pore volume is 0.27cm 3 / g, BET specific surface area is 187m 2 / g.
[0093] Comparative Example 2
[0094] Weigh 330 g of small-pore pseudo-boehmite (P-DF-03), 28 g of basic nickel carbonate, 103 g of ammonium heptamolybdate, and 27 g of ammonium dihydrogen phosphate and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0095] Weigh 40 g of polyethylene glycol 3000 and dissolve it in 50 g of ethanol. Add the ethanol solution of polyethylene glycol into the primary mixture and continue mixing to obtain a mixture.
[0096] 100 g of aqueous ammonia (ammonia content: 25%) and 10 g of deionized water were added, the pH was maintained at 10, and the mixture was stirred to obtain a mixed material.
[0097] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 1.5 mm.
[0098] The catalyst was dried in an oven at 120°C for 2 hours and calcined at 500°C for 3 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 65.0wt%, MoO3 25.0wt%, NiO 5.0wt% and P2O 55.0wt%. The pore size of the catalyst is 6nm and the pore volume is 0.31cm 3 / g, BET specific surface area is 192m 2 / g.
[0099] Comparative Example 3
[0100] Weigh 300 g of macroporous pseudo-boehmite (YH-05), 64.5 g of nickel nitrate hexahydrate, 103 g of ammonium heptamolybdate, and 27 g of ammonium dihydrogen phosphate, and mix them in a kneader for 60 minutes to obtain a primary mixture.
[0101] Weigh 40 g of polyethylene glycol 3000 and dissolve it in 50 g of ethanol. Add the ethanol solution of polyethylene glycol into the primary mixture and continue mixing to obtain a mixture.
[0102] The mixed material is kneaded into a plastic body for 1 hour to form a preform with elasticity. The preform is extruded to obtain a molded material; in the extrusion process, the mold is a clover-shaped mold with an opening diameter of 1.5 mm.
[0103] The catalyst was dried in an oven at 120°C for 2 hours and calcined at 500°C for 3 hours to obtain an oxide sample of the catalyst. Based on the total weight of the catalyst, each component is expressed in the form of oxides. The catalyst composition includes: Al2O3 65.0wt%, MoO3 25.0wt%, NiO 5.0wt% and P2O 55.0wt%. The pore size of the catalyst is 7nm and the pore volume is 0.33cm 3 / g, BET specific surface area is 188m 2 / g.
[0104] Test Example 1
[0105] 1.0 g of catalyst was weighed and loaded into a stainless steel reactor. Before use, the catalyst was in-situ sulfurized by introducing sulfurized oil with a CS2 mass fraction of 5% and H2 to sulfurize nickel, cobalt, molybdenum, and tungsten metal oxides into sulfides. The sulfurization conditions were: temperature 300 ° C, mass space velocity 1.5 h -1 , pressure of 6.0MPa, hydrogen-to-oil ratio of 600:1, time of 5h. The acid value of the waste wind turbine gear lubricating oil used is 0.76mgKOH / g, the S content is 3320ppm, and the P content is 163ppm. The reaction conditions of hydrogenation refining are: temperature of 300℃, pressure of 7.0MPa, mass space velocity of 1.5h -1 , the hydrogen-oil ratio is 600:1. The lubricating oil indicators after hydrogenation with different catalysts are shown in Table 1.
[0106] Table 1
[0107]
[0108]
[0109] Examples 1-7 are catalysts prepared by different components and preparation methods, which show good catalytic performance in the process of hydrofining of waste wind turbine gear lubricating oil. Due to its large pore size and pore volume structure, it is conducive to the mass transfer and diffusion of macromolecular reactants in the catalyst pores, and can realize the hydrogenation removal of oxygen, sulfur, phosphorus and other components in lubricating oil additives, which is manifested as acid value, sulfur content, and phosphorus content significantly lower than that of waste raw material oil. Compared with Example 1, Comparative Example 1 does not add polyethylene glycol pore expander during the preparation of the catalyst, nor does it peptize under alkaline conditions. The pore size and pore volume of the prepared catalyst are significantly reduced compared with Example 1. Compared with Example 1, the aluminum raw material used in the preparation of the catalyst is small-pore pseudo-boehmite, and the pore size and pore volume of the prepared catalyst are significantly reduced compared with Example 1. Compared with Example 1, Comparative Example 3 adds polyethylene glycol pore expander during the preparation of the catalyst, but does not peptize under alkaline conditions. The pore size and pore volume of the prepared catalyst are significantly reduced compared with Example 1. From the evaluation results, it can be seen that the acid value, sulfur content and phosphorus content in the hydrogenation refined products of the catalysts prepared in Comparative Examples 1, 2 and 3 are much higher than those in the examples, proving that the hydrogenation removal effect of elements such as oxygen, sulfur and phosphorus in the raw base oil is very poor, thereby proving that the catalyst for hydrogenation of wind turbine gear lubricating oil proposed in the present invention has good technical effects.
[0110] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a hydrotreating catalyst, characterized in that: The following steps are involved: (1) mixing macroporous pseudo-boehmite, a nickel or cobalt oxide precursor, a molybdenum or tungsten oxide precursor, and a phosphorus oxide precursor to obtain a primary mixture; (2) adding the alcohol solution of the pore-enlarging agent to the primary mixture and continuing to mix to obtain a mixture; (3) adding an alkaline peptizing agent and water to the mixed material, maintaining the pH value at 9-12, to obtain a mixed material; (4) kneading the mixed material into a plastic body, extruding strips, and obtaining a molding material; (5) drying and calcining the molded material to obtain the hydrotreating catalyst; The pore size of the macroporous pseudo-boehmite is ≥10nm; the pore volume is ≥1.0cm 3 / g.
2. The method for preparing a hydrotreating catalyst according to claim 1, characterized in that: The pore expanding agent is polyethylene glycol; preferably, the pore expanding agent is polyethylene glycol 3000, polyethylene glycol 4000, polyethylene glycol 6000 or polyethylene glycol 8000; preferably, the amount of the pore expanding agent added is 8-20wt% of the macroporous pseudo-boehmite; and / or The alcohol solution of the pore expanding agent is a C1-C4 saturated monohydric fatty alcohol solution of the pore expanding agent, preferably an ethanol solution of the pore expanding agent.
3. The method for preparing a hydrotreating catalyst according to claim 1, characterized in that: The alkaline peptizing agent is ammonia water, triethylamine or ethylenediamine; preferably, the addition amount of the alkaline peptizing agent is 2-20wt% of the mixed material; more preferably, the peptization reaction time of the mixed material is 0.5-1.0h.
4. The method for preparing a hydrotreating catalyst according to claim 1, characterized in that: The pore size of the macroporous pseudo-boehmite is 10-12 nm, and the pore volume is 1.0-1.2 cm 3 / g, specific surface area is 350-400m 2 / g.
5. The method for preparing a hydrotreating catalyst according to claim 1, characterized in that: The oxide precursor of nickel is basic nickel carbonate or nickel hydroxide; the oxide precursor of cobalt is basic cobalt carbonate or cobalt hydroxide; the oxide precursor of molybdenum is ammonium heptamolybdate or ammonium tetramolybdate; the oxide precursor of tungsten is ammonium tungstate or ammonium metatungstate; and the oxide precursor of phosphorus is diammonium phosphate.
6. The method for preparing a hydrotreating catalyst according to claim 1, characterized in that: Based on the total weight of the hydrotreating catalyst, the content of NiO or Co2O3 is 5-10wt%, the content of MoO3 or WO3 is 20-28wt%, the content of P2O5 is 5-8wt%, and the content of Al2O3 is 54-70wt%.
7. The method for preparing a hydrotreating catalyst according to claim 1, characterized in that: In the extrusion process of step (4), the mold used is a clover-shaped mold with an opening diameter of 1.5-3 mm; in step (5), drying is performed at a temperature of 100-120° C. for 2-5 hours; and roasting is performed at a temperature of 400-600° C. for 3-5 hours.
8. A hydrotreating catalyst, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7; Preferably, the pore size of the hydrotreating catalyst is 12-18 nm and the pore volume is 0.5-0.8 cm 3 / g, BET specific surface area is 100-203m 2 / g.
9. Use of the hydrotreating catalyst prepared by the preparation method according to any one of claims 1 to 7 or the hydrotreating catalyst according to claim 8 in the hydrotreating of lubricating oil, wherein the lubricating oil is preferably waste lubricating oil of fan gears.
10. A method for hydrofining waste lubricating oil of fan gears, characterized in that: The hydrorefining method uses the hydrorefining catalyst prepared by the preparation method according to any one of claims 1 to 7 or the hydrorefining catalyst according to claim 8; Preferably, the hydrotreating catalyst is in situ sulfurized by introducing sulfurized oil with a CS2 mass fraction of 1-10% and H2 before use. The sulfurization conditions are: temperature of 300-340°C, mass space velocity of 1-3h -1 , pressure is 4.0-6.0MPa, hydrogen-oil ratio is 400:1-800:1, time is 4-8h; Preferably, the hydrofining method includes the following reaction conditions: temperature of 250-350°C, pressure of 5.0-15.0 MPa, mass space velocity of 0.5-1.5 h -1 , the hydrogen-to-oil ratio is 400:1-800:1.